The Students’ Difficulties in Essay Writing during Pandemic Covid- 19 in English Language Education of Universitas Islam Riau - Arimuliani Ahmad; Fitria Andriani; Maya Yova Dita Mulyani; Rahma Sarita; Rahmah Hazimah Anita (UIR Press, 2022)
Online learning during the Covid-19 era requires educators to be creative in compiling interesting learning materials so that students can study the material well and not get bored while learning. But in reality, some of the problems faced by some students, especially those in semester 4th of the English department at the Universitas Islam Riau Riau who have been online since the beginning of the COVID-19 pandemic in 2020, have difficulty when they are writing an essay. The sample of this research is the English Language Education student in Universitas Islam Riau, which consist of 34 fourth semester students. This was investigation design which mainly analyzes quantitative data via a distributed web-based questionnaire provided as numerical data on graphics and charts. This questionnaire was based on Ceylan's (2019) questionnaire which focus on knowledge, attitudes, and behaviors. The majority of online learning aspects are connected to distance and time flexibility, student and instructor interaction, and many aspects that online learning shares with distant education. As a result, online learning may not even be ready to serve all disciplines in the same way, and that not all online learning platforms are the same. The student lacked the opportunity to practice academic writing skills and produce a solid essay product. As a result, students must practice writing as often as possible in order to produce a well-written essay. Cognitive difficulties are now defined as difficulties in the categories of writing perspective, transferring language, and writing process.